Optimal timing to transfer embryos for women who underwent hysteroscopy: a systematic review and meta-analysis - Chang Liu; Zhiqi Liao; Lei Cai; Xueqi Gong; Yanan Li; Yunan He; Yinwei Chen (BMC Pregnancy and Childbirth)
Abstract Objective This study aimed to investigate the optimal time interval between hysteroscopy and embryo transfer. Methods Electronic databases including PubMed, Embase, and Cochrane Library were searched up to Jul 2021. Two authors selected the articles independently and extracted data regarding study characteristics, quality, and results. A random-effect model was employed, and summary risk ratios (RR) at 95% confidence intervals (CI) were calculated. Results A total of 2123 patients from 5 studies were included. Pooled results showed that no significant differences for clinical pregnancy rates within 50-day and 90-day time interval comparison groups (RR = 0.83, 95% CI 0.61–1.11, P = 0.21; and RR = 0.91, 95% CI 0.74–1.12, P = 0.38, respectively), whereas clinical pregnancy rate was significantly increased in patients with a waiting interval of ≤ 120 days (RR = 0.75, 95% CI 0.61–0.93, P = 0.009). Subgroup analysis demonstrated that transferring embryos within 50 days for patients with normal uterine cavities was associated with a higher live birth rate (RR = 0.71, 95% CI 0.54–0.95, P = 0.02). Conclusion This meta-analysis identified that performing embryo transfer within 120 days for patients who underwent adhesiolysis and polypectomy within 50 days for patients who underwent diagnostic hysteroscopy was associated with superior outcomes, respectively. These findings may provide evidence to guide clinical decisions for reproductive clinicians. The conclusions might be limited by the small publication numbers. Further studies with a larger sample size were recommended.